HISTORICAL REPRESETATION OF GRAHAM SWIFT’S WORKS - Priyanka Bala (International Journal of Multidisciplinary Research and Studies, 2021)
This essay demonstrates that in Graham Swift's Last Orders, the past is represented by the figure of Jack Dodds, a deceased man who is perceived as a living presence and whose life is associated with a book of requests, wishes, and unwritten rules regarding the way the living should behave. This essay also demonstrates that Jack Dodds's life is associated with a book of requests, wishes, and unwritten rules regarding the way the dead should behave. This concept is shown by a remark that was made by Linda Hutcheon (2002), who said that "understanding the past becomes an issue of representation, that is of creating and interpreting, not of objective recording". Hut The characters in the novel that was written by Graham Swift do their best to understand these requirements and rules, and they abide by them out of a sense of duty and respect for the power that they have. Because these principles do not exist in written form, we have to infer them from the guidance included in Jack's figurative book of life. This is the information that Jack's loved ones and close friends are most likely to recollect and discuss. If the past is depicted as a book of unwritten rules that the contemporary characters are required to discern and obey, then there are a number of different ways in which the past might be understood. It has been shown to us that in order for the world of the present to carry out its aims and obligations, it only obeys the commands provided to it by the world of the past. The modern civilization that we now inhabit does not put a significant focus on either the uniqueness of its values or the ideals themselves.